Structured Training Program About Breast Self Examination Toward Awareness and Behavior Among Women in Bengkulu City, Indonesia - Jipri Suyanto; Sianipar, Berlian Kando; Danur Azissah Roeliana Sofais; Santhna Letchmi Panduragan (YCAB Publisher, 2024)
Background:Indonesia, an emerging country, faces a substantial mortality rate due to breast cancer. This high mortality rate is largely attributed to a lack of knowledge and health literacy among women, which limits their ability to independently seek and understand relevant health information. As a result, a significant proportion of breast cancer patients are only informed that their cancer is in an advanced stage during health assessments, often due to worsening health conditions. Breast cancer carries a significant risk of mortality. Objective:The aim of this study was to examine the influence of a structured training program on breast self-examination (BSE) on women's awareness and behavior. Methods:This study employed a two-group quasi-experimental design involving women aged 26 to 35 over a period of 4 months. Awareness and behavior were assessed before and after receiving organized training. A self-designed questionnaire was utilized, which was validated for its reliability. The sampling technique used was purposive sampling. A total of 250 participants were included, with 125 in the intervention group and 125 in the control group. An unpaired group comparison test of awareness and behavior data was performed using the Mann-Whitney test to evaluate the differences between the control and treatment groups after the intervention. Results:The mean ± standard deviation of awareness in the control group was 45.12 ± 15.830 before the intervention and 47.96 ± 16.754 after. The mean score for post-intervention awareness in the control group was 13.67. The mean rank for awareness in the intervention group increased from 64.69 before the intervention to 45.87 after. The average rank for behavior in the control group increased from pre-control to post-control, reaching 31.80, while the behavior in the intervention group increased from pre-control to post-control, reaching 45.87. Conclusion:The results revealed a significant difference between the control group and the intervention group. A structured training program can effectively improve awareness and behavior related to routine breast self-examinations. Keywords: structured training program; breast self-examination; awareness; behavior